20 years of the SMART protein domain annotation resource. Issue Volume 46:Issue D1(2018) (10th October 2017) - Letunic, Ivica; Bork, Peer
Abstract: SMART (Simple Modular Architecture Research Tool) is a web resource (http://smart.embl.de ) for the identification and annotation of protein domains and the analysis of protein domain architectures. SMART version 8 contains manually curated models for more than 1300 protein domains, with approximately 100 new models added since our last update article (1). The underlying protein databases were synchronized with UniProt (2), Ensembl (3) and STRING (4), doubling the total number of annotated domains and other protein features to more than 200 million. In its 20th year, the SMART analysis results pages have been streamlined again and its information sources have been updated. SMART's vector based display engine has been extended to all protein schematics in SMART and rewritten to use the latest web technologies. The internal full text search engine has been redesigned and updated, resulting in greatly increased search speed.